Improving mother–infant interaction during infant feeding: A randomised controlled trial in a low‐income community in South Africa. Issue 6 (15th July 2020) - Tomlinson, Mark; Rabie, Stephan; Skeen, Sarah; Hunt, Xanthe; Murray, Lynne; Cooper, Peter J
ABSTRACT: Background: Maternal–infant feeding interactions are a primary context for engagement between mothers and their infants, and constitute a unique space in which reciprocity, attunement and maternal sensitivity can be expressed. Increasingly, research demonstrates the importance of the psychological and social nature of the feeding context, and how it may be affected by maternal mental state, feeding skills and sensitivity. As such, feeding interactions may provide useful contexts for observations of maternal sensitivity, reflecting well on day‐to‐day maternal sensitivity. Aims and Objectives: This paper is a post hoc examination of the impact of an intervention on maternal sensitivity during a feeding interaction when the infants were 6 months old. Participants: A total of 449 women consented to participate in the original intervention and were randomly assigned to the intervention or control groups. Mothers and infants were assessed during pregnancy, and then at 2, 6, 12 and 18 months of infant age. At the 6 month follow‐up visit, 79% (354 out of 449) of the participants were retained. Post hoc analyses were conducted on the original sample to determine breastfeeding status. Sixty‐nine percent of the women completed the feeding observation at the 6 months follow‐up visit, of which 47% reported exclusively breastfeeding and 22% reported bottle‐feeding. Results: Results demonstrated that during a feeding interaction, maternal sensitivity was significantly improved among non‐breastfeeding mothers who received the intervention. Particularly, maternal responsiveness to infant cues and synchronous interactions was higher among non‐breastfeeding intervention mothers compared to control group mothers. The results also show that non‐breastfeeding mothers who received the intervention were significantly less intrusive in their interactions with their infants. Conclusion: The intervention had particular beneficial effects for mothers who were not breastfeeding and suggest that the intervention offered a protective effect for non‐breastfeeding mothers. RESUMEN: Trasfondo: Las interacciones materno‐infantiles de alimentación son un contexto primario de compromiso interactivo entre madres y sus infantes. Alimentar al infante es un proceso complejo que requiere no sólo que se provean los nutrientes, sino también una relación social entre el cuidador y el infante. Metas y Objetivos: Este artículo es un examen a posteriori del impacto de una intervención sobre la sensibilidad materna durante una interacción de alimentación cuando los infantes tenían seis meses de edad. Participantes: Un total de 449 mujeres consintieron en participar en la intervención original y fueron asignadas al azar a la propia intervención o a los grupos de control. A la visita de seguimiento de los seis meses, el 79% (354 de las 449) de las participantes aún se mantenían. Se llevaron a cabo análisis a posteriori en el grupo muestra original para determinar la condición de amamantamiento. Resultados: Durante una interacción de alimentación, la sensibilidad materna mejoró significativamente entre las madres que no amamantaban y que recibieron la intervención. La sensibilidad materna a las señales del infante y a las interacciones sincrónicas fue más alta entre madres de la intervención que no amamantaban tal como se les comparó con las madres del grupo de control. Conclusión: Estos resultados demuestran particularmente los efectos beneficiosos para las madres en el grupo de intervención que no estaban amamantando, y sugieren que la intervención ofreció un efecto de protección para las madres que no amamantaban. RÉSUMÉ: Contexte: Les interactions maternelles‐bébé durant l'alimentation sont un contexte primaire pour l'engagement entre les mères et leurs bébés. Nourrir son bébé est un processus complexe qui inclut non seulement le transfert d'éléments nutritifs mais également une relation sociale entre la personne prenant soin du bébé et le bébé. Buts et Objectifs: Cet article est une étude post hoc de l'impact d'une intervention sur la sensibilité maternelle durant une interaction d'alimentation lorsque les bébés avaient six mois. Participantes: Un total de 449 femmes ont consenti à participer à l'intervention originelle et ont été réparties au hasard au groupe d'intervention ou au groupe de contrôle. A la visite de suivi de six mois 79% (354 sur 449) des participantes ont été retenues. Les analyses post hoc analyses ont été faites sur l'échantillon d'origine afin de déterminer le statut d'allaitement au sein. Résultats: Durant une interaction d'alimentation, la sensibilité maternelle a été améliorée de manière importante chez les mères de donnant pas le sein qui recevaient l'intervention. La réaction maternelle aux signes du bébé et les interactions synchronisées étaient plus élevées chez les mères du groupe d'intervention de non allaitement au sein comparées au groupe de mères de contrôle. Conclusion: Ces résultats dénotent des effets particulièrement favorables pour les mères du groupe d'intervention qui n'allaitaient pas au sein, et suggèrent que l'intervention a offert un effet protecteur pour les mères n'allaitant pas leurs bébé au sein. ZUSAMMENFASSUNG: Verbesserung der Mutter‐Kind‐Interaktion während des Fütterns: Eine randomisierte, kontrollierte Studie in einer einkommensschwachen Gemeinde in Südafrika Hintergrund: Die Interaktion zwischen Mutter und Kind beim Füttern stellt einen primären Kontext in der Mutter‐Kind‐Beziehung dar. Das Füttern eines Säuglings ist ein komplexer Prozess, bei dem nicht nur Nährstoffe weiter gegeben werden, sondern auch eine soziale Beziehung zwischen Bezugsperson und Säugling entsteht. Untersuchungsziele: In dieser Studie wurden die Effekte einer Intervention auf die mütterliche Sensibilität während einer Fütterungsinteraktion mit sechs Monate alten Säuglingen post‐hoc untersucht. Teilnehmerinnen: Insgesamt 449 Frauen erklärten sich mit einerr Teilnahme an der ursprünglichen Intervention einverstanden und wurden nach dem Zufallsprinzip den Interventions‐ oder Kontrollgruppen zugeordnet. Bei dem Follow‐up‐Besuch nach 6 Monaten blieben 79% (354 von 449) der Teilnehmerinnen der Studie erhalten. An der ursprünglichen Stichprobe wurden Post‐hoc‐Analysen durchgeführt, um den Stillstatus zu bestimmen. Ergebnisse: Die Sensibilität beim Füttern wurde bei nicht stillenden Müttern, die die Intervention erhalten hatten, signifikant verbessert. Die mütterliche Reaktionsfähigkeit auf die vom Säugling ausgehenden Zeichen und die Synchronität der Interaktion war in der Gruppe der nicht stillenden Mütter, die die Intervention erhalten hatten, höher als bei den Müttern der Kontrollgruppe. Fazit: Diese Ergebnisse zeigen die insbesondere für nicht stillende Mütter vorteilhafte Wirkung der Intervention und legen nahe, dass die Intervention eine schützende Wirkung auf nicht stillende Mütter hatte. 抄録: 授乳中の母‐乳児の相互作用を改善する:南アフリカの低所得者地域における無作為化比較対照試験 背景:母‐乳児の授乳中の相互作用は、母親とその乳児間の没頭に関する最初の 重要な場面である。乳児の授乳は、栄養を運ぶということだけでなく、養育者と 乳児間の社会的な関係が伴う複雑な過程である。 目的:本論文は、乳児が6ヶ月の際の授乳の相互作用時に母親の感受性に対する 介入の影響の事後調査である。 対象者:449人の女性が最初の介入に参加することに同意し、介入群かコントロ ール群に無作為に割り当てられた。6ヶ月児のフォローアップの訪問で、79% ( 449人の内354人) の対象者が保持された。母乳育児の状態の測定のために事後分 析が元のサンプルに実施された。 結果:授乳中の相互作用において、母親の感受性は、介入群の母乳育児をしてい ない母親において有意に向上した。乳児の合図に対する母親の応答と同調相互作 用は、コントロール群の母親に比べ、母乳育児をしていない介入群の母親の方が 高かった。 結論:これらの結果は、母乳育児をしていない介入群の母親に対して特に優位に 効果があることを実証し、介入が母乳育児でない母親について保護効果を提供し ていることを示唆している。 摘要: 研究背景:母婴喂养互动是母婴互动的主要内容。婴儿喂养是一个复杂的过程, 不仅涉及营养物质的转移, 还涉及照顾者与婴儿之间的社会关系。研究目的:本文是对六个月大的婴儿在喂养互动过程中, 采取干预行为对母亲敏感性的影响进行的事后检验。研究对象:共有449名妇女同意参与到最初的干预行为中, 她们被随机分配到各个干预组或对照组。在六个月的随访中, 79% (354/449) 的参与者被保留下来。我们对原始样本进行了事后分析, 以确定母乳喂养的状况。检验结果:在喂养互动中, 接受干预的非母乳喂养母亲的母亲敏感性显著提高。与对照组母亲相比, 非母乳喂养干预组的母亲对婴儿提示和同步互动的回应更积极。研究结论:检验结果表明, 干预组中非母乳喂养的母亲尤为受益, 干预行为对其具有保护作用。 ملخص: تحسين التفاعل بين الأم والرضيع أثناء الإطعام: تجربة معشاة ذات شواهد في مجتمع منخفض الدخل في جنوب أفريقيا الخلفية: التفاعلات بين الأمهات والرضع هي سياق أساسي للمشاركة بين الأمهات وأطفالهن. وإطعام الرضع عملية معقدة لا تنطوي على نقل المغذيات فحسب، بل تشمل أيضا ً علاقة اجتماعية بين مقدم الرعاية والرضيع. الأهداف: هذه الورقة هي دراسة بعدية لتأثير التدخل التجريبي على حساسية الأم أثناء تفاعل التغذية عندما كان عمر الرضع ستة أشهر. المشاركون: وافق مجموعة من 449 امرأة على المشاركة في التدخل الأصلي وتم تعيينهن عشوائياً في المجموعة التجريبية أو الضابطة. وفي زيارة المتابعة التي استمرت ستة أشهر، تم الاحتفاظ بنسبة 79 في المائة (354 من أصل 449) من المشاركين. أجريت تحليلات بعدية على العينة الأصلية لتحديد حالة الرضاعة الطبيعية. النتائج: خلال تفاعل التغذية، تحسنت حساسية الأمهات بشكل كبير بين الأمهات غير المرضعات اللاتي تلقين التدخل. كانت استجابة الأمهات لإشارات الرضع والتفاعلات المتزامنة أعلى بين الأمهات غير المرضعات في المجموعة التجريبية مقارنة بأمهات المجموعة الضابطة. الاستنتاج: تُظهر هذه النتائج آثاراً مفيدة بشكل خاص للأمهات في مجموعة التدخل التي لم تكن ترضع رضاعة طبيعية، وتشير إلى أن التدخل كان له أثر وقائي على الأمهات غير المرضعات.